Accessibility of Elderly Citizens to Basic Facilities In Akure Metropolis in Nigeria - Musilimu Adeyinka Adetunji (Department of Architecture, Faculty of Engineering, Universitas Diponegoro, Indonesia., 2020)
This study examined the accessibility of elderly citizens to some basic services in Akure metropolis. This was carried out with a view to determine the patterns of distribution and accessibility of these services in the city. Primary and secondary data were employed for this study. Geographical Positioning System was used to capture the coordinates of important locations and of some basic facilities such as Public Tertiary Hospital, Primary Health care centre and banks in the city. Nearest Neighbour Analysis was used to calculate the mean distance travel to some basic services from 13 major localities in Akure metropolis. Descriptive and inferential statistics were employed to analyse the data. Finding reveals that some basic facilities are not evenly distributed across different localities in Akure. The mean distance travel to Public Tertiary Hospital is 3.36kms. The pattern of distribution of Public Tertiary Hospital is dispersed rather than random. More than 60% of the elderly rely on public transport services for their trip to access some basic facilities in the city. Traffic delay was ranked highest (66%) among the problems militating against the effective utilisation of urban facilities in Akure metropolis. The study recommends that more basic facilities should be provided in localities where such services are lacking. This would reduce long distance trip to these facilities in the city. The study concludes that better transport services should be made available at reasonable transport fares in order to promote accessibility of the elderly and other segments of the population to urban facilities in Akure and similar other cities in Nigeria.